2015
DOI: 10.1007/s00216-015-9112-5
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized electrospun poly(vinyl alcohol) nanofibers for on-chip concentration of E. coli cells

Abstract: Positively and negatively charged electrospun poly(vinyl alcohol) (PVA) nanofibers were incorporated into poly(methyl methacrylate) (PMMA) microchannels in order to facilitate on-chip concentration of Escherichia coli K12 cells. The effects of fiber distribution and fiber mat height on analyte retention were investigated. The 3D morphology of the mats was optimized to prevent size-related retention of the E. coli cells while also providing a large enough surface area for analyte concentration. Positively charg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 43 publications
0
32
0
Order By: Relevance
“…Therefore, electrospun matrices have been recently adopted within bioanalytical microfluidic systems to enhance sample preparation (filtration, separation, and concentration) and analyte detection [87][88][89]. In some of these applications, water-soluble nanofibers have been used to facilitate on-chip reagent storage in microfluidic biosensors through the immobilization of biological molecules directly within fiber-spinning dopes [89,90].…”
Section: Hybrid Lab-on-a-chip Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, electrospun matrices have been recently adopted within bioanalytical microfluidic systems to enhance sample preparation (filtration, separation, and concentration) and analyte detection [87][88][89]. In some of these applications, water-soluble nanofibers have been used to facilitate on-chip reagent storage in microfluidic biosensors through the immobilization of biological molecules directly within fiber-spinning dopes [89,90].…”
Section: Hybrid Lab-on-a-chip Devicesmentioning
confidence: 99%
“…In alternative, non-water-soluble electrospun nanofibers have been variously functionalized and used as a substrate for microfluidic HIV immunoassays [78], Escherichia coli detection [88], and on-chip sample concentrators [87]. To this aim, standard immobilization procedures have been purposely modified to functionalize nanofiber mats after being bonded into microfluidic channels [88,91]. In these applications, the non-water-soluble nanofibers could withstand the fluid flow within the channels, dramatically increasing the functional surface area available within the devices.…”
Section: Hybrid Lab-on-a-chip Devicesmentioning
confidence: 99%
“…Finally, grafting nylon nanofiber media using other methods such as plasma treatments, or by chemical cross‐linkers, may provide the ability to fine‐tune mesh and fiber diameter sizes postelectrospinning without causing the losses in membrane stability observed here. The variation of the electrolytic properties of spun nanofiber membranes for antibody functionalization has already proved successful . Furthermore, a series of stacked membranes with tailored morphologies, perhaps even assembled using other design processing techniques such as ultra‐sonic bonding, may provide initial solutions for the first prototypes in light weight, highly flexible, and sensor driven face‐mask design…”
Section: Grafted Membrane Properties Reduce Sustained Aerosol Capturementioning
confidence: 99%
“…The variation of the electrolytic properties of spun nanofiber membranes for antibody functionalization has already proved successful. 57 Furthermore, a series of stacked membranes with tailored morphologies, perhaps even assembled using other design processing techniques such as ultra-sonic bonding, may provide initial solutions for the first prototypes in light weight, highly flexible, and sensor driven face-mask design. 44…”
Section: Grafted Membrane Properties Reduce Sustained Aerosol Capturementioning
confidence: 99%
“…It was found that three layers sparse negatively charged NFs significantly reduced the non specific analyte (bacteria) retention (17%), whereas positive charged NFs were used for the detection of different concentrations of E. coli K12 (87%). For this work, polyclonal anti E. coli antibodies were immobilized via EDC/sulfo-NHS chemistry on negatively charged NFs in order to selectively capture the negatively charged E. coli cells over 60 min using a syringe flow system and counted the number of colonies in the resulted effluent (low-average number of colonies in inlet solution was 62 CFU/mL) [57].…”
Section: Microfluidic Biochipsmentioning
confidence: 99%